2022
DOI: 10.3399/bjgpo.2022.0126
|View full text |Cite|
|
Sign up to set email alerts
|

Hormone replacement therapy prescribing in menopausal women in the UK: a descriptive study

Abstract: BackgroundRecent studies on the prescribing of hormonal replacement therapy (HRT) medicines to treat symptoms of menopause are lacking.AimTo describe the prescribing of HRT in a cohort of UK menopausal women.Design & settingPopulation-based drug utilization study using IQVIA Medical Research Database.MethodPrimary care data of women with recorded menopause and/or 50 years and older between January 2010 and November 2021 were extracted from the database. The incidence rate (IR) of women who received their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Such inconsistencies in WHI guidelines may explain the regained acceptance of HT, with a steady increase in the number of women receiving their first prescription for HT. 28 The present study also possesses several limitations to consider in future research. We did not compare with a control group without HT, which is a reason for further study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Such inconsistencies in WHI guidelines may explain the regained acceptance of HT, with a steady increase in the number of women receiving their first prescription for HT. 28 The present study also possesses several limitations to consider in future research. We did not compare with a control group without HT, which is a reason for further study.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, WHI results did not evaluate the mortality or the causal link between HT and breast cancer. Such inconsistencies in WHI guidelines may explain the regained acceptance of HT, with a steady increase in the number of women receiving their first prescription for HT 28 …”
Section: Discussionmentioning
confidence: 99%
“…These changes in the incidence trend likely reflect a reduced effect of the initial incidence increases brought about by mammography screening in the UK introduced from the late 1980s or a possible effect of a decline in usage of hormone replacement treatment. 27 28 However, the effect of hormone replacement treatment on breast cancer risk is small in comparison to other risk factors, 7 and trends in this treatment has varied over time, such as changes in preferred formulations, doses, and treatment durations, 29 30 31 which may impact breast cancer risk levels. 32 33 As has been reported elsewhere, 34 35 36 mortality for breast cancer has declined substantially despite the incidence increase, which is indicative of improvements in early detection (including through screening 37 ) and improved treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a small study reported that women receiving DHA supplementation had lower increases in EPA and higher DHA:EPA ratios if they were taking oral HRT compared to those not on HRT, suggesting reduced retroconversion of DHA to EPA (128) . Increasingly, periand postmenopausal women are now being prescribed transdermal oestrogen (rather than oral) (129) , due to its efficacy in resolving menopausal symptoms and a superior safety profile. Transdermal oestrogen treatments are applied at much lower doses and are metabolised differently to oral treatments, avoiding first-pass hepatic metabolism to pass directly into the bloodstream.…”
Section: Causes Of Differential Cvd Risks Throughout the Female Life ...mentioning
confidence: 99%